(untitled) (Bioagro, 2022)
The multiplication of arbuscular mycorrhizal fungi (AMF) spores is a limitation for agricultural applications as biofertilizers. In the present study, a massive multiplication of AMF from cocoa farms (Theobroma cacao L.) in the San Martín region, Peru, was carried out to optimize their handling and spore production under controlled environmental conditions. The experiment was conducted under greenhouse conditions in a completely randomized design, considering three sources of AMF inoculum obtained in the provinces of Mariscal Cáceres, Lamas and Rioja, in two periods (110 and 220 days) and two host crops (maize and rice). This material was mixed with one volume of sand and three volumes of agricultural soil, which were placed in crates. At the end of the periods, the population of spores, mycorrhizal colonization, height of the host plant, and the dry weight of the aerial part and root were evaluated. Rice acts as a suitable host and multiplies a greater number of AMF spores. The treatment based on the mycorrhizal inoculum from Mariscal Cáceres multiplied with rice plants at 220 days, presented the highest population of spores. Therefore, it could be used as a methodology for massive propagation of AMF due to its great reproduction capacity.